Japan : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper describes determinants of Japan's productivity growth, reform outputs, and speculation on future potential growth. It investigates the macroeconomic implications of alternative fiscal strategies; examines the issues surrounding the Bank of Japan's understanding of price stability and monetary policy; examines the impact of Japan's inflation and price developments; and describes the reengagement of Japanese banks with the rest of Asia for maintaining financial and macroeconomic stability in both Japan and in the other Asian countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet